Two Spectrophotometric Methods Based on Diazotization Coupling Reaction for Determination of Genistein in Pure and Supplement - Mohammed, Farqid F.; Abed, Sadeem Subhi (Iraqi Journal of Science, 2023)
Genistein (GEN) is one of the predominant dietary isoflavones found in legumes such as soybeans. Genistein has been recommended as an osteoporosis treatment for postmenopausal women and elderly men, with the intention of reducing cardiovascular disease and hormone-dependent malignancies. Therefore, two sensitive and simple methods for quantifying it in the supplements preparation were developed.The first method (A) comprised employing the surfactant Triton X-114 to extract the result of the diazotization reaction with 4-Aminoacetophenone(4AMA) utilizing a cloud point extraction technique. The product was extracted using micelles of a non-ionic surfactant (TritonX-114) and then spectrophotometrically detected at a specified wavelength of 437nm. The linearity of the calibration curve was in the range of 0.25 -2.75 µg/mL of GEN(r = 0.9978) under optimal conditions. The average sample recovery was determined to be between 96 and 101 %. For 2 µg/mL of GEN, the relative standard deviation (RSD) was (0.27%). The second method (B) involved using the spectrophotometric-flow injection methodology for the same diazotization coupling reaction described above, and  the orange colored dyewas measured at a   wave length of 437 nm.Calibration curve were linear at different concentration range of GEN 10 to 100 µg/mL , relative standard deviation RSD% were 0.23 to 1.21. The proposed methods were applied to determine the presence of GEN in Supplements.